Coulson and Richardson's chemical engineering. - Ray, Ajay K.; Coulson, J. M. (John Metcalfe); Richardson, J. F. (John Francis) (Butterworth-Heinemann, 2018)
Coulson and Richardson's Chemical Engineering: Volume 2B, Separation Processes, Sixth Edition, covers distillation and gas absorption, illustrating applications of the fundamental principles of mass transfer. Several techniques, including adsorption, ion exchange, chromatographic membrane separations and process intensification are comprehensively covered and explored.